Increase in alcohol related deaths: is hepatitis C a factor?. Issue 9 (1st September 2002) - Henry, J A; Moloney, C; Rivas, C; Goldin, R D
Abstract : Aim: To evaluate recent trends in alcohol related deaths in the UK and to consider possible causative factors. Design: Observational retrospective study of the database of the Office for National Statistics, alcohol consumption data reported by the General Household Survey, and other published data. Setting: England, 1993–9. Results: Deaths for each million of the population from alcohol related illness increased by 59% in men and 40% in women over the years 1993 to 1999. One subgroup of alcohol related deaths, ICD 571.3 (alcoholic liver damage unspecified), showed a 243% increase in men aged 40 to 49 years over the same period. Figures for younger men, and women in all age groups, showed less pronounced increases. There has been no associated rise in alcohol intake. There has been an increase in the incidence of hepatitis C virus (HCV) infection in recent years, and alcohol consumption in HCV positive individuals accelerates the progression to cirrhosis. Circumstantial evidence links the rise in HCV infection to the use of illicit drugs in the 1970s and 1980s, among those currently aged 40 to 59 years. Conclusions: The recent increase in alcohol related deaths cannot be solely explained by a change in drinking habits. It is suggested that this probably results from the rapid progression of alcoholic cirrhosis in people who have acquired HCV infection through intravenous drug use. Alcohol consumption in HCV positive individuals is firmly linked with a poor outcome.